Perancangan Buku Ilustrasi Karakter Jajanan Tradisional Khas Surabaya dengan Teknik Vektor Guna Meningkatkan Minat Anak pada Produk Lokal - Swandawidharma, Yohanes Ev; Bahruddin, Muh; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2016)
Traditional snacks currently almost alienated and less attractive to Surabaya residents, especially the children because of the emergence of a wide range of modern snacks. This happens because of lack of awareness of local people to appreciate and preserve the genuine products from the area of Surabaya. Traditional snacks including one culture that must be preserved, therefore the purpose of this research is to design book character illustration of traditional snacks Surabaya to improve a child's interest in local products. Traditional snacks are part of the culture of each city in Indonesia where the snacks are. In the midst of modern meal in Surabaya, which serves a variety of selection, Surabaya typical traditional snacks began to be forgotten among the children. From the analysis of these data, obtained keyword